(untitled) (Brazilian Journal of Radiation Sciences, 2021)
Analysis of historical artifacts, it’s a multidisciplinary field of research known as archaeometry, has expanded greatly in recent years. One of the reasons for this expansion was the great effort of physicists and engineers, who focused on the development of portable instruments, that allow analyses in situ and non-destructive of these artifacts. The X-Ray Fluorescence (XRF) is techniques of the most used in this field of study. In this work the XRF was used to analysis the artwork "Passagem de Humaitá", by the Brazilian painter Victor Meirelles, dated 1872. The painting, which has dimensions of 268 cm x 405 cm, is exposed at National Historical Museum located in Rio de Janeiro. The analyses were carried out in situ with portable XRF system model TRACER IV from Bruker, which has Rh anode and can operate with maximum voltage and current of 40 kV and 200 μA. Spectra of more than 80 points of the painting were obtained, with the tube operating at voltage of 40 kV and a current of 10 μA, and the spectra were collected during 60 seconds. The results allowed to conclude that the painter used pigments such as vermilion and/or cinnabar [HgS], calcite [CaCO3], zinc white [ZnO], lead white [(PbCO3)2·Pb(OH)2], red ocher [Fe2O3], brown umbra [Fe2O3.MnO2].